Market-supporting institutions, institutional complementarities and economic growth: new evidence on the nonlinear relationship - Mohd Ali, Ly Slesman @ Sulaiman (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Recent existing literature overwhelmingly focuses on direct effects of “cluster” institutions on growth largely ignoring the indirect or indexing role of institutions and the interaction effects between different dimensions of institutional matrix in influencing long-run growth process. One contention suggests different domains of institutions are inter-related in equilibrium whole, with any changes in one domain may influence the rest of domains—the so-called “institutional complementarity hypothesis”. This study aims to empirically examine this hypothesis based on the sample of 93 developed, emerging market and developing countries over 1980-2010 periods using novel threshold regression framework. Using Rodrik’s (2000, 2005) conceptualization to unbundle market-supporting institutions (MSI) into market-creating (MCI), market-regulating (MREGI), market-stabilizing (MSTABI) and market-legitimizing (MLEGI) institutions, this paper investigates whether countries belong to regime with high MCI quality have efficiently transformed Solow-Mankiw-Romer-Weil (Solow-MRW) growth determinants, MREGI, MSTABI, and MLEGI into higher growth compare with low quality MCI regime. The finding reveals that countries obtaining MCI quality above an estimated optimum threshold value (i.e. high-MCI regime) can transform Solow-MRW growth determinants and MREGI into higher growth than those falls below (i.e. low-MCI group). It finds weak support for MSTABI and no support for MLEGI that they each matter differently in low- and high-MCI regime. These findings are invariant to extensive robust tests. One important policy implication is that poor countries can have high productivity gains from factor inputs and efficient functioning of regulatory institutions from sufficient improvement in the quality of MCI.